The new reverse mortgage formula : - Kelly, Tom (Wiley, 2005)
The New Reverse Mortgage Formula explains reverse mortgages in easy language so seniors and their family members can fully understand and benefit from these useful loan products. Reverse loans allow seniors to convert part of their home equity into tax-free income, letting seniors easily borrow against the value of their home without selling it. Safer than ever, today’s reverse mortgages are non-recourse loans and lenders do not share in any appreciation or accrued equity. Safe and simple, reverse mortgages are a valuable option for senior homeowners having trouble living on a fixed income or in need of extra cash for any unforeseen expense